(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective of Study: To determine the causes of low amniotic fluid for pregnant women Methodology: A descriptive study was carried out on (100) pregnant and post pregnant women had diagnosis with low amniotic fluid in Bint Al-Huda Hospital for the period from (3 March to 11April 2019). Validity and reliability of questionnaire are determined through pilot study. Descriptive and inferential statistical procedures were used to analyze the data, and the data were collected by using interview technique, constructed questionnaire designed and developed for the purpose of the study. Results: Results of the study showed that the highest percentage of the study sample were within the age group (20-25 years). And (44%) of the study sample were graduated from secondary school and more than half of the study sample were housewife, and residents in urban areas. 41% of the study sample of the current pregnancy duration were (32-36), the interval between the last pregnancy and current one year to two years, (76%) of the study sample have multigravida and have no history of previous abortion. And that the cause of low amniotic fluid from a medical point is the (35%) due to pregnancy induced hypertension, (25%) of the study sample due to Premature rupture of membranes (PROM) and (20%) of the study sample due to placental problems.